2019
DOI: 10.1177/0741088319862512
|View full text |Cite
|
Sign up to set email alerts
|

Discourses in Teachers’ Talk about Writing

Abstract: Views about what writing is and how it should be taught have varied over the years as well as across contexts. Studies of curricula, teaching materials, and teaching practices have shown a strong focus on skills, genres, and processes, but few have asked teachers about their perspectives on writing. In this article we explore what views, or discourses, of writing are currently active among teachers in Swedish compulsory education, covering ages from 7 to 15. Sixty teachers answered a questionnaire with open an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 18 publications
(48 reference statements)
1
23
0
6
Order By: Relevance
“…Learning is related to disciplinary literacy, and focuses on the content of the current school subject. In line with Sturk and Lindgren (2019), this discourse appears above all in interactions concerning grades 7-9. This might be explained by a stronger focus on the content as such.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Learning is related to disciplinary literacy, and focuses on the content of the current school subject. In line with Sturk and Lindgren (2019), this discourse appears above all in interactions concerning grades 7-9. This might be explained by a stronger focus on the content as such.…”
Section: Discussionsupporting
confidence: 60%
“…Further, the lack of a socio-political discourse is emphasised. Earlier studies have also identified a negotiation of discourses in teachers' talk about practice and that teachers position themselves in a combination of discourses (McCarthey et al, 2014;Sturk & Lindgren, 2019). This negotiation and positioning can be regarded as possibilities for agency, for both teachers and pupils (Holmberg E. Sturk, A.-C. Randahl & C. Olin-Scheller 4 & Wirdenäs, 2010;Randahl, 2012).…”
Section: Discourses Of Writing In School Practicementioning
confidence: 98%
See 2 more Smart Citations
“…Ivanič’s framework has been used for different analytical purposes such as assessment, academic writing and students’ perceptions of writing and learning to write (Wohlwend, 2009; Baker, 2011; Lundgren, 2013; Lambirth, 2016) but important contributions have been made in relation to curriculum studies. Concerning the relationship between curriculum documents and teachers’ perspectives and practices on writing, Sturk and Lindgren (2019) investigated 60 teachers’ views in Swedish compulsory education (7–15 years of age) in relation to three themes: ‘how teachers work with writing, what they think is most important in writing, and how they evaluate pupils’ writing’ (p. 507). Their views revealed the dominance of the process discourse which was combined with the discourses of creativity, skills and genre.…”
Section: Discourses Of Writing As a Framework For Understanding Writing In Different Educational Contextsmentioning
confidence: 99%